1994
DOI: 10.1111/j.1600-0773.1994.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deltamethrin on Regional Brain Polyamines and Behaviour in Young Rats

Abstract: The present study examines the mechanism of neurotoxic action of a synthetic pyrethroid formulation deltamethrin in young rats. Newly weaned Wistar Albino male rats received deltamethrin of technical grade at a dose of 7.0 mg/kg body weight/day in corn oil, orally from postnatal day 22 to postnatal day 37. Deltamethrin significantly decreased the wet weight of the hippocampus without much affecting the weight of cerebellum, pons medulla, hypothalamus, frontal cortex and corpus striatum in comparison to respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 25 publications
(14 reference statements)
4
23
0
1
Order By: Relevance
“…According to Ayub- Shah et al (1996) cypermethrin with lower dose resulting mild disorganization of hepatic laminae and higher dose produced necrosis of hepatic cells, with pyknotic nuclei and dilatation of sinusoids with highly disrupted hepatic laminae 21 . In addition, the findings from the current histological observation are in accord with diverse earlier studies which indicated that the introduction to cypermethrin and other pesticides led to provoke intensive physiological, biochemical, histological turbulence in different experimental animals as rat [17], mice [21], rabbit [22], cat [23], broiler chicks [24] and fish [25]. The similar results are reported for malathion, endosulphon and other pesticides indicating exposure of these pesticide leading to encourage histological disturbances in experimental animals [26, 27 and 28].…”
Section: Discussionsupporting
confidence: 90%
“…According to Ayub- Shah et al (1996) cypermethrin with lower dose resulting mild disorganization of hepatic laminae and higher dose produced necrosis of hepatic cells, with pyknotic nuclei and dilatation of sinusoids with highly disrupted hepatic laminae 21 . In addition, the findings from the current histological observation are in accord with diverse earlier studies which indicated that the introduction to cypermethrin and other pesticides led to provoke intensive physiological, biochemical, histological turbulence in different experimental animals as rat [17], mice [21], rabbit [22], cat [23], broiler chicks [24] and fish [25]. The similar results are reported for malathion, endosulphon and other pesticides indicating exposure of these pesticide leading to encourage histological disturbances in experimental animals [26, 27 and 28].…”
Section: Discussionsupporting
confidence: 90%
“…Clinical manifestations of acute Deltamethrin poisoning have been documented in occupationally and accidentally exposed cases. Moreover, a number of studies on the side effects of this insecticide have been detailed, including neurotoxicity, immune-suppression and allergy [ 5,6,7], hypertension [8], decreased testosterone levels [9] and genotoxic, immunotoxic and tumorogenic effects of Deltamethrin in mammalian and non-mammalian species [10,11]. The main reaction involved in the metabolism of Deltamethrin in mice and rats is ester cleavage mainly due to the action of carboxyesterase.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous injection of deltamethrin at the dose of 12.5 mg/kg produced severe neuronal loss in the hippocampus and in cortical areas of rats, and this neuronal death involved both necrosis and activation of markers of apoptotic death (Wu and Liu, 2000). It was also reported that orally treatment with deltamethrin at a dose of 7.0 mg/kg/BW produced neuropathological damage in brains in rats (Husain et al, 1994). In the morphology results, degeneration and necrosis morphological characteristics obviously were appeared in hippocampal neurons and astrocytes in 0.92 and 1.8 mg/kg-dose group mice, such as pyknosis, karyorrhexis, breakup and lysis of nuclear membrane.…”
Section: Discussionmentioning
confidence: 96%